2003
DOI: 10.1002/ffj.1178
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of essential oils from needles, branches and cones of Pinus pinea, P. halepensis, P. pinaster and P. nigra from central ltaly

Abstract: The composition of the essential oils from the needles, branches and female cones of four species of Pinaceae, Pinus pinea, P. halepensis, P. pinaster and P. nigra, has been analysed and comparative chemical evaluations were obtained. In P. pinea the major compound of the essential oils of all the three plant parts is limonene (58.9–62.5%), in P. halepensis α‐pinene (18.1%–53.6%) and myrcene (13.7–42.1%), in P. pinaster α‐pinene (24.7–40.4%) and β‐pinene (21.7–29.2%), and in P. nigra α‐pinene (28.4–61.7%). Cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
113
3
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 15 publications
17
113
3
6
Order By: Relevance
“…halepensis has been used in traditional therapeutic practice such as Italian popular medicine as well as decoctions of leaves, buds, resin. Pinus spp young female cones are used to treat respiratory diseases, cough, colds and rheumatic pains 16 . It has also been found that the resin and decoction of all pine trees have antiseptic, diuretic, rubefacient, vermifuge, antidiabetic and cicatrisant properties 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…halepensis has been used in traditional therapeutic practice such as Italian popular medicine as well as decoctions of leaves, buds, resin. Pinus spp young female cones are used to treat respiratory diseases, cough, colds and rheumatic pains 16 . It has also been found that the resin and decoction of all pine trees have antiseptic, diuretic, rubefacient, vermifuge, antidiabetic and cicatrisant properties 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…is one of the major tree species in terms of the area it covers, and of ecological and economic values (Quézel, 2000). It is rich in secondary metabolites (Pasqua et al, 2002;Macchioni et al, 2003;Maestre et al, 2003;Robles et al, 2003) that could play an important role in secondary succession because of its allelopathic potential (Gallet and Pellissier, 1997;Fernandez et al, 2006Fernandez et al, , 2008Fernandez et al, , 2009) and its autotoxicity when regenerating (Fernandez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of components was made on the basis of their retention indices on nonpolar (HP-5) and/or on polar (PEG) columns and by computerised matching of the acquired mass spectra with those stored in the spectrometer data base using Willey mass spectral library and with the literature [16][17][18].…”
Section: Component Identificationmentioning
confidence: 99%